2004
DOI: 10.1038/sj.bjc.6602109
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour efficacy of VEGFR2 tyrosine kinase inhibitor correlates with expression of VEGF and its receptor VEGFR2 in tumour models

Abstract: During the development of indazolylpyrimidines as novel and potent inhibitors of vascular endothelial growth factor (VEGF) receptor-2 (VEGFR2) tyrosine kinase, we observed that some human tumour xenografts are more sensitive to VEGFR2 kinase inhibitors than others. A better understanding of the basis for this differential response may help to identify a predictive marker that would greatly aid in the identification of a suitable patient population for treatment. One representative compound from the indazolylpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Currently, multiple strategies to inhibit the VEGF pathway, and specifically those directed to the receptors of VEGF Flk1/ KDR, are under clinical development. In in vitro and in vivo models, they show antitumoral and anti-angiogenic activity [34,35]. These novel therapies would benefit especially those patients whose adenomas were incompletely resected and may progress.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiple strategies to inhibit the VEGF pathway, and specifically those directed to the receptors of VEGF Flk1/ KDR, are under clinical development. In in vitro and in vivo models, they show antitumoral and anti-angiogenic activity [34,35]. These novel therapies would benefit especially those patients whose adenomas were incompletely resected and may progress.…”
Section: Discussionmentioning
confidence: 99%
“…This had the advantage of allowing for the distinction between human (tumorderived) plasma VEGF and mouse (host-derived) sVEGFR-2 using ELISAs specific for the human and mouse proteins. Cells from human prostate line PC3, previously shown to have a low level of VEGF expression compared with other tumor cell types (39), were transfected to overexpress human VEGF 165 and clones expressing various levels of human VEGF 165 were isolated. Two distinct cell lines were derived, one with elevated VEGF expression, named ''PC3 VEGF-high '', and one with low levels of VEGF, named ''PC3 VEGF-low '', Parental and transfected variants were incubated for 24 h in vitro in serum-free medium and conditioned medium and then tested for VEGF; PC3 VEGF-high cells expressed >1,500-fold VEGF-low variants expressed levels of VEGF below the detectable range of the ELISA kit (Fig.…”
Section: Vegf Modulates Svegfr-2mentioning
confidence: 99%
“…In this study, bevacizumab had no significant effect on tumour growth. The role of VEGF in sustaining the growth of PC-3 xenografts is difficult to ascertain as Takei et al (2004) showed siRNA against VEGF could reduce xenograft growth, but Dev et al (2004) showed that PC-3 cells expressed little VEGF and were not sensitive to a VEGFR2 inhibitor. The poor efficacy of 2-MeOE2 in vivo was further highlighted by its lack of activity in the PC-3 model, despite daily dosing at 100 mg kg À1 p.o.…”
Section: Discussionmentioning
confidence: 99%